Investigation of Poly(3,4-ethylenedioxythiophene):Poly(styrenesulfonate) Hole Transport Layer for Solution-Processed Polymer Solar Cells - Chengxi Zhang; Jiang Cheng; Xiaoqing Liao; Xiaojuan Lian; Jin Zhang; Xin Yang; Lu Li (International Journal of Photoenergy)
The inverted polymer solar cell was prepared by self-made spray-coating system, and the poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) hole transport layer was studied. 220 nm poly-(3-hexylthiophene):[6,6]-phenylC61butyric-acid methyl-ester (P3HT:PCBM) and 40 nm PEDOT:PSS were deposited on ZnO thin film subsequently by solution spray coating. Different volume of isopropyl alcohol was introduced into PEDOT:PSS to decrease the contact angle and obtain the optimum Marangoni flow. The surface morphology and roughness of PEDOT:PSS films were characterized by atomic force microscopy with varied deposition temperature from 70°C to 160°C. The improvement of power conversion efficiency (PCE) was attributed to the enhancement of vertical phase separation in PEDOT:PSS film, which improved the charge transfer in the bulk cell. The highest PCE of spray-coated PSCs reached 2.80% after postannealing for 10 min.